Caveolin‐1‐driven membrane remodelling regulates hnRNPK‐mediated exosomal microRNA sorting in cancer. Issue 4 (8th April 2021) - Robinson, Harley; Ruelcke, Jayde E.; Lewis, Amanda; Bond, Charles S.; Fox, Archa H.; Bharti, Vandhana; Wani, Shivangi; Cloonan, Nicole; Lai, Andrew; Margolin, David; Li, Li; Salomon, Carlos; et al.
Abstract: Background: Caveolae proteins play diverse roles in cancer development and progression. In prostate cancer, non‐caveolar caveolin‐1 (CAV1) promotes metastasis, while CAVIN1 attenuates CAV1‐induced metastasis. Here, we unveil a novel mechanism linking CAV1 to selective loading of exosomes with metastasis‐promoting microRNAs. Results: We identify hnRNPK as a CAV1‐regulated microRNA binding protein. In the absence of CAVIN1, non‐caveolar CAV1 drives localisation of hnRPNK to multi‐vesicular bodies (MVBs), recruiting AsUGnA motif‐containing miRNAs and causing their release within exosomes. This process is dependent on the lipid environment of membranes as shown by cholesterol depletion using methyl‐β‐cyclodextrin or by treatment with n‐3 polyunsaturated fatty acids. Consistent with a role in bone metastasis, knockdown of hnRNPK in prostate cancer PC3 cells abolished the ability of PC3 extracellular vesicles (EV) to induce osteoclastogenesis, and biofluid EV hnRNPK is elevated in metastatic prostate and colorectal cancer. Conclusions: Taken together, these results support a novel pan‐cancer mechanism for CAV1‐driven exosomal release of hnRNPK and associated miRNA in metastasis, which is modulated by the membrane lipid environment. Abstract : Highlights 1. Non‐caveolar caveolin‐1 drives non‐canonical localization of hnRNPK to multivesicular bodies (MVB) via membrane raft‐dependent mechanism. 2. MVB localized hnRNPK mediates EV loading of AsUGnA motif‐containing miRNA, which is required for EV‐induced in vitro osteoclastogenesiss. 3. Elevated EV hnRNPK in biofluids from metastatic cancer patients suggest a role as a biomarker.